2010
DOI: 10.1001/archsurg.2010.156
|View full text |Cite
|
Sign up to set email alerts
|

A New and Simplified Technique for Laparoscopic Gastric Bypass in a Residency Training Program

Abstract: Introduction of S-LGB has resulted in excellent outcomes and significant reductions in resource utilization while enhancing opportunities for resident teaching and full participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Specifically, laparoscopic RYGB provides the key components to develop important advanced laparoscopic techniques, which include gastric resection and pouch creation, jejunojejunostomy, and gastrojejunostomy, provide varying aspects of laparoscopic tissue mobilization, stapling, and suturing anastomoses. 13,14,17 In our review, laparoscopic RYGB was uniformly one of the most commonly performed procedures among academic centers and would provide the perfect platform for surgical resident training in advance laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, laparoscopic RYGB provides the key components to develop important advanced laparoscopic techniques, which include gastric resection and pouch creation, jejunojejunostomy, and gastrojejunostomy, provide varying aspects of laparoscopic tissue mobilization, stapling, and suturing anastomoses. 13,14,17 In our review, laparoscopic RYGB was uniformly one of the most commonly performed procedures among academic centers and would provide the perfect platform for surgical resident training in advance laparoscopic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…5 Martin et al found an overall decrease of early complications from 15 to 5% and a significant decrease in anastomotic strictures using a simplified technique. 28 Fanous et al reported increased rates of acute renal failure from 0% to 0.82% (p=0.047). 6 This study found a non-significant effect on excess weight loss (64% vs. 66%).…”
Section: Effects On Surgical Outcomementioning
confidence: 97%
“…The average difference in operation time is a decrease of 9.6 minutes (range -93 to +40 minutes). After exclusion of studies that showed decreased operating room (OR) times due to simplification of the operative procedure 28 , or severe inclusion bias 24 , OR time was increased by 29.3 minutes (range +13 to +40 minutes).…”
Section: Effects On Surgical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty with training surgical residents in LRYGBP arises from the requirement for advanced laparoscopic skills39. Naturally, proficiency in these skills is often achieved only by the trainee's senior or chief year.…”
Section: Strategies For Ex Vivo Training In Laparoscopic Roux‐en‐$\fomentioning
confidence: 99%